2016
DOI: 10.1080/22201181.2016.1234664
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative management of ETT and LMA cuff pressures: a survey of anaesthetists’ knowledge, attitude and current practice

Abstract: Background: Endotracheal tubes and laryngeal mask airway devices are routinely used during anaesthesia. Inappropriate inflation of cuffs has been shown to cause postoperative airway morbidity, and limiting the pressure decreases the incidence of pharyngo-laryngeal complications. Subjective measurements of cuff pressures correlate poorly to actual pressures, yet the use of objective cuff manometry is not routinely practised. The aim of this study was to determine current clinical practice of cuff inflation as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
(39 reference statements)
0
7
0
4
Order By: Relevance
“…In our multicentre study encompassing both anaesthesia and critical care staff only 31.1% of the care providers knew the correct Pcuff, 97% had never used a tracheal cuff manometer, while 81% were aware that improper cuff pressure could harm patients. Meanwhile, a seemingly higher knowledge of the correct tracheal cuff pressure was recorded by 45% of participants in a multicentre questionnaire-based survey conducted among 160 anaesthesiologists practicing in South Africa [ 15 ]. In the South African study the participants were all anaesthesiologists (anaesthesia faculty fellows, residents and diplomates), while in our study and the others, the participants were an admixture of physician and non-physician care providers (nurse anaesthetists, certified registered nurse anaesthetists, student registered nurse anaesthetists, anaesthesia technicians, ICU nurses, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our multicentre study encompassing both anaesthesia and critical care staff only 31.1% of the care providers knew the correct Pcuff, 97% had never used a tracheal cuff manometer, while 81% were aware that improper cuff pressure could harm patients. Meanwhile, a seemingly higher knowledge of the correct tracheal cuff pressure was recorded by 45% of participants in a multicentre questionnaire-based survey conducted among 160 anaesthesiologists practicing in South Africa [ 15 ]. In the South African study the participants were all anaesthesiologists (anaesthesia faculty fellows, residents and diplomates), while in our study and the others, the participants were an admixture of physician and non-physician care providers (nurse anaesthetists, certified registered nurse anaesthetists, student registered nurse anaesthetists, anaesthesia technicians, ICU nurses, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…This applies to the endotracheal tube, but also the tracheostomy tube and laryngeal mask airway. However, with the reports from the United Kingdom and South Africa, it would appear that beside making the manometer available, deficits in knowledge and attitude regarding Pcuff management need to be addressed too [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Det kan skje gjennom undervisning og økt bevisstgjøring om risiko ved å ikke bruke en cufftrykkmanometer både på larynxmaske og endotrakealtube. Å utarbeide standarder, retningslinjer eller prosedyrer basert på forskning vil også bidra til å styrke en implementering og endre praksis (34,39).…”
Section: Diskusjonunclassified
“…Although ETT cuff pressure management techniques include the predetermined volume technique, palpation technique, syringe technique, and minimal occlusive volume technique, the gauge manometer is the most reliable manual measurement and is widely recommended 5,6,19 (Siamdous et al, 2015AQ4). However, a gauge manometer is not routinely used in actual practice in some ICUs, 19 and previous studies highlighted that the subjective practice of estimation using finger palpation still exists among practitioners, for example, in Pakistan, 14 Sri Lanka, 5 Egypt (Khalil et al, 2018), Malaysia, 20 Italy, 21,22 India, 23 South Africa, 24 and the United States, 6 among others. An observational cross‐sectional study in Melbourne, Australia, which assessed the minimal leak test and cuff manometer techniques, noted that the minimal leak test results in a cuff pressure outside the recommended range; thus, the authors suggested the use of the cuff manometer technique for reliable practice 25 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, another recent study reported that more than 70% of clinicians in Pakistan have never used a manometer in their practice 14 . The unavailability of manometers was also noted as a reason for not using it routinely in studies conducted among anaesthetists in South Africa 24 and India (Balakrishan & Jacob, 2016). Akhtar 29 and Abubaker et al 14 suggested that gauge manometer usage should be made mandatory, and education regarding its use should be disseminated among clinicians for better application in daily practice to safeguard patients against life‐threatening complications.…”
Section: Introductionmentioning
confidence: 99%